(untitled) (Research, Society and Development, 2022)
Introduction: The counting of the number of steps is a great advantage to assess behaviors related to the health indicators of the population, including school-age children. Objective: To analyze the quality of time index between the number of daily steps, life and body life. Methodology: This is a cross-sectional study with two classes of the 1st year of a municipal school in Aracaju, Brazil. The sample consisted of 31 students of both sexes aged between 6 and 8 years. The number of steps was performed using pedometers. Anthropometric information on weight and height, quality of life (AUQEI questionnaire), daytime sleepiness (Pediatric Daytime Sleepiness Scale) and sleep time (daily record) were collected. Descriptions and guarantees were performed. Results: Most children had a good quality of life and enough sleep time. We observed life and positive evaluation between the number of steps in school and quality quality scoreho; p = 0.01). Conclusion: The number of steps in school is correlated with children’s quality of life. , are more studies that help to improve the relationship of the number of steps in the school environment.